Composition of the suppliers in the value chain of the automotive industry of Durango: Composición de los proveedores en la cadena de valor de la industria automotriz de Durango - Hernandez Chavarria, Juana; González Lazalde, Ivan; Galván Ismael, María Quetzalcihuatl (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2023)
Define the characteristics of the supply companies linked to an automotive company, inquire about the position of the value chain, and supplier development. Information was collected from 30 companies directly linked to the company's production process. A descriptive analysis of the main characteristics of these is presented. To know their differences, the information obtained was subjected to hypothesis tests applying non-parametric statistics through the Kruskal-Wallis test and the Mann Whitney test. Supplier companies are mainly small and medium-sized, delivery times for national companies are shorter than for foreign ones, national companies are limited by their ability to obtain additional machinery compared to foreign companies, the latter maintain a greater negotiating capacity and carry out MTP. The oldest have global capitalization. The large ones are more rigid in their negotiation policies and the small ones are affected by the client's negotiation capacity, sometimes presenting a captive relationship. The bigger, the better position the supplier companies have in the value chain in terms of diversity of clients and foreign capital. The results obtained provide information on the conditions in which the supplier companies linked to an automotive company relate to it and the position they hold in the value chain.